Efektivitas Pemberdayaan peer group support terhadap Peningkatan Kepatuhan Pengobatan pada Klien Tuberkulosis: a systematic review - Yanta , Hardi; Permatasari , Henny; Mulyono , Sigit; Nursasi , Astuti Yuni (Fakultas Farmasi Universitas Tjut Nyak Dhien, 2025)
First The prevalence of tuberculosis shows a global increase, so a sustainable management strategy is needed. The peer group support approach provides a space for continuous interaction between peer educators and peer groups, which allows for more intensive information delivery to improve treatment adherence in tuberculosis patients. Purpose This systematic review aims to assess the effectiveness of peer group support interventions in improving treatment adherence in tuberculosis clients. Methods: A literature search was conducted using PRISMA guidelines, through several databases PubMed, Clinical Key, Science Direct, Proquest for articles published between 2020 and 2024. Results: Peer group support interventions have been shown to significantly improve treatment adherence in pulmonary tuberculosis clients. Social support from peer groups contributes significantly to strengthening client regularity in the therapy schedule. This approach is considered more effective because group members not only transfer knowledge gained from educators and personal experiences, but are also able to identify and resolve problems faced independently. Peer group support interventions have been proven effective in improving treatment adherence in tuberculosis clients.